The Concept of Youth Social Etiquette Based on Moral Education Values in Surah An-Nur Verses 30-31 - Hidayatul Putri; Rosdialena (Konsultan Jurnal Ilmiah Indonesia, 2026)
Modern moral degradation demands a resilient ethical guide for the younger generation, particularly in establishing boundaries for cross-gender interactions to prevent deviations from religious guidelines. This study aims to thoroughly examine the framework of adolescent social etiquette derived from the moral education values implicit in Surah An-Nur, verses 30–31. Employing a qualitative library research method combined with a textual analysis (tafsir tahlili) approach, this paper evaluates the textual meanings of these verses while contextualizing them within the current realities of youth behavior. The findings indicate that both verses lay down structural pillars for social relationships, which fundamentally center on the mandate to restrain the gaze (ghaddul bashar) and safeguard personal honor. Cultivating these values within the lives of the younger generation serves as an upstream preventive instrument to counter promiscuity and moral decay. Ultimately, this concept of etiquette does not merely restrict outward physical conduct; it shapes internal spiritual consciousness to foster a social interaction ecosystem that is healthy, honorable, and compliant with Islamic principles.